Studentification, diversity and social cohesion in post-socialist Budapest - Fabula, Szabolcs; Boros, Lajos; Kovács, Zoltán; Horváth, Dániel; Pál, Viktor (Hungarian Geographical Bulletin, 2017)
In the literature studentification is closely associated with gentrification. Many authors consider the mass invasion of students to inner-city neighbourhoods as a type of gentrification, some of them even use the two terms interchangeably. Regardless of theoretical considerations, it seems that there is a consensus on the significance of studentification in contemporary urban transformations. Recent studies demonstrate that the appearance of students as ’transient’ inhabitants in inner-city neighbourhoods, accompanied by growing differences in lifestyles and socio-cultural attitudes weakens social cohesion in the affected neighbourhoods Haase, A. et al. 2012). This study focuses on the interplay between studentification, socio-cultural diversity and social cohesion in an inner-city district of Budapest, Józsefváros. The district has been characterised by several waves of urban rehabilitation and subsequent gentrification since the transition of 1989-1990. Studentification has also become dominant phenomenon in the area due to the settling of new higher education institutions, the concomitant influx of students, as well as low rent and dwelling prices providing a niche for the spontaneous movements of a new generation of urbanites (Grabkowska, M. 2011; Bernt, M. et al. 2015). The main research questions we intend to answer in this paper are as follows. Firstly, what is the relationship between studentification and gentrification in Józsefváros? Secondly, what kinds of effects has the influx of students on the social cohesion of the district? According to our findings, studentification in Józsefváros is not the pioneer phase of gentrification, but - especially in the rehabilitation areas - it runs more or less parallel with it. Most of the students use the place as a springboard in their career, and after graduation most of them leave. The attitude of students is, however, very much resembles those of the young, highly educated newcomers, i.e. early gentrifiers. The impacts of studentification on the social milieu of Józsefváros are contradictory. On the one hand, the inflow of students and young intellectuals increases the socio-cultural diversity of the district, contributing to the recognition of diversity in a post-socialist context, and fostering tolerance and the acceptance of different cultures and lifestyles. On the other hand, it seems that the ongoing population change hampers the establishment of strong social ties at the neighbourhood level and leads to certain conflicts.